Code Mixing Used by Tutors at Bananaina English Course - Johan, Andrian Nuriza; Hartina, Tri (English Education and Literature Journal (E-Jou), 2025)
The investigation centers on tutors’ code-mixing at Bananaina English Course during 2023–2024. The objectives encompass discerning code-mixing variants employed by instructors and unraveling their underlying motivations. This inquiry adopts a qualitative descriptive approach, spotlighting three English educators. Data collection entailed interviews, direct observation, and audio documentation, then interpreted through Muysken’s (2000) and Hoffmann’s (1991) frameworks. Findings reveal alternation code-mixing predominated (53%, 84 utterances), followed by insertion (28%, 45 utterances) and congruent lexicalization (19%, 31 utterances). Tutors engaged in code-mixing chiefly to elucidate concepts and foster rapport. Examining code-mixing illuminates linguistic adaptation in diverse settings and enriches comprehension of language acquisition in multilingual milieus. Such insights may refine pedagogical strategies in heterogeneous classrooms. Moreover, code-mixing research elucidates the psychological and sociocultural dimensions of linguistic variation, shedding light on dynamics of power, identity, and communicative norms.